A taxonomy of the scope and organization of local sexually transmitted disease services for policy and practice. (December 2018) - Rodriguez, Hector P; Starling, Summer; Kandel, Zosha; Weech-Maldonado, Robert; Moss, Nicholas J; Silver, Lynn
Local health departments (LHDs) and their organizational partners play a critical role in controlling sexually transmitted diseases (STDs) in the United States. We examine variation in the differentiation, integration, and concentration (DIC) of STD services and develop a taxonomy describing the scope and organization of local STD services. LHD STD programs (n = 115) in Alabama (AL) and California (CA) responded to surveys assessing STD services available in 2014. K-means cluster analysis identified LHD groupings based on DIC variation. Discriminant analysis validated cluster solutions. Differences in organizational partnerships and scope of STD services were compared by taxonomy category. Multivariable regression models estimated the association of the STD services organization taxonomy and five-year (2010–2014) gonorrhea incidence rates, controlling for county-level sociodemographics and resources. A three-cluster solution was identified: (1) low DIC (n = 74), (2) moderate DIC (n = 31), and (3) high DIC (n = 10). In discriminant analysis, 95% of jurisdictions were classiﬁed into the same types as originally assigned through K-means cluster analysis. High DIC jurisdictions were more likely (p < 0.001) to partner with most organizations than moderate and low DIC jurisdictions, and more likely (p < 0.001) to conduct STD needs assessment, comprehensive sex education, and targeted screening. In contrast, contact tracing, case management, and investigations were conducted similarly across jurisdictions. In adjusted analyses, there were no differences in gonorrhea incidence rates by category. Jurisdictions in CA and AL can be characterized into three distinct clusters based on the DIC of STD services. Taxonomic analyses may aid in improving the reach and effectiveness of STD services.